PATH38 When is it safe to return to driving after a first-ever seizure?. Issue 11 (22nd October 2010) - Brown, W; Lawn, N; Pearlman, D; Shields, S; Lee, J; Somerville, E; Dunne, J
Abstract : Introduction: The risk of recurrence following first-ever seizure is about 50% warranting driving restriction during the period of highest risk. In the UK, the duration of nondriving following a first unprovoked seizure with low risk of recurrence has recently been reduced from 12 to 6 months. The acceptable chance of occurrence of a seizure in the next year (COSY) has been estimated to be 30% (2.5%/month) for driving a private vehicle. We aimed to ascertain when the risk of recurrence is consistently lower than 2.5%/month as this may represent an appropriate time to allow return to driving. Method: 1100 adults with a first-ever seizure (provoked or unprovoked) seen at three teaching hospitals were prospectively evaluated between 1999 and 2008. Patients ineligible to drive were excluded. Seizure recurrence was evaluated using Kaplan–Meier analysis. Results: The cumulative probabilities of seizure recurrence at 3, 6 and 12 months were 23, 33 and 41%. Overall the probability of recurrence fell below 2.5% per month during the 7th month (8th month for all unprovoked seizures and during the 5th month for provoked seizures). If, as suggested by the UK Driver and Vehicle Licencing Agency, a risk of less than 20% (1.67%/month) is acceptable a period of 10 months is required for patients with unprovoked seizures including those with normal investigations. Conclusions: Our data do not support a reduction in the driving restriction for patients with first-ever unprovoked seizure to less than 8 months.